If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -1w)(5w + -6) = 0 Reorder the terms: (5 + -1w)(-6 + 5w) = 0 Multiply (5 + -1w) * (-6 + 5w) (5(-6 + 5w) + -1w * (-6 + 5w)) = 0 ((-6 * 5 + 5w * 5) + -1w * (-6 + 5w)) = 0 ((-30 + 25w) + -1w * (-6 + 5w)) = 0 (-30 + 25w + (-6 * -1w + 5w * -1w)) = 0 (-30 + 25w + (6w + -5w2)) = 0 Combine like terms: 25w + 6w = 31w (-30 + 31w + -5w2) = 0 Solving -30 + 31w + -5w2 = 0 Solving for variable 'w'. Factor a trinomial. (-5 + w)(6 + -5w) = 0Subproblem 1
Set the factor '(-5 + w)' equal to zero and attempt to solve: Simplifying -5 + w = 0 Solving -5 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + w = 0 + 5 w = 0 + 5 Combine like terms: 0 + 5 = 5 w = 5 Simplifying w = 5Subproblem 2
Set the factor '(6 + -5w)' equal to zero and attempt to solve: Simplifying 6 + -5w = 0 Solving 6 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5w = 0 + -6 -5w = 0 + -6 Combine like terms: 0 + -6 = -6 -5w = -6 Divide each side by '-5'. w = 1.2 Simplifying w = 1.2Solution
w = {5, 1.2}
| 75=3(45-6-5k-6) | | x^2-12xy+32y^2=0 | | 6x^2+-12x=0 | | 4347+6x=x | | 3x^2+10x+20=0 | | x+3x-10=22 | | w-3+2w=9 | | 1/2(4x-8)=12 | | 7.2+x/2=8.8 | | X+3x-10=9 | | 0=x^2-9x+18 | | (9x+16)2=81 | | f(x)=6x^2+6x-5 | | x^2+1.4x+1.96=0 | | 8x+26=60x | | 3t^2+16t+21= | | 21/3x-2=7/x | | (a)-3/4=-5/8 | | 87*76= | | -4(2x+3)=5(x-3) | | X-1/4x4 | | (3-2i)/(4-3i) | | 1/2x+1/2x=x+1 | | (2t)-5=7 | | 250+50=40h | | 2x+8=4x-3 | | (2/3)x=-18 | | 1.1+1.2x-5.4=44 | | x^2+(364/x) | | 7(2m-3)-3(4m+8)=-2 | | 3c^2-2c-24=0 | | I=(8500)rt |